SISTEM INFORMASI PRAKTEK KERJA LAPANGAN DI PT. BAKRIE PIPE INDUSTRIES - Indah Dwijayanthi Nirmala; Hendarman Lubis (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2019)
Field work practice is one of the activities by carried out students and as one of the graduation requirements students . But until now the process of submitting fieldwork practices has not yet utilized technology-based website, with this information system Technology to facilitate the process submission of field work practices because it can be used anytime and anywhere. Therefore, a web-based work practice information system was built in order to make it easier for vocational students and students in the process of submitting practice field work. In the process of making this application using language PHP programming, CodeIgniter framework and MySQL database. Method the software development used in this system is the Rapid Model Application Development (RAD). For application testing carried out using Blaxbox. The results of this study are able to help students in submitting fieldwork practices become faster and easy.